Degree in Rural Education: Intentions in the Training of Field Educators in Marajó - Eliane Miranda Costa (Pontificia Universidad Católica del Perú, 2017)
The text is the result of the master survey conducted in the city of Portel, in the archipelago of Marajó. It ims to discuss the intentions of forming educators of the field from the Bachelor,s Degree in Rural Education. Methodologically it is a case study of one type of qualitative approach, which collected the data using the following techniques: semi-structured interviews, non-participant observation, closed questionnaire and document analysis. The data analyzed in the light of the content analysis technique in dialogue with theorists, like Arroyo (2011), Caldart (2010), Molina (2010) and others, made it possible to consider that one of the forming intentions is the conquest of new schools not in the sense of a new physical structure, but an open space for dialogue and debate.